Artificial Intelligence and Educational Practice. The Case of The Myths that Inhabit Us. From Prometheus to Marvel - Zapata Romano, Rafael Alejandro (2025)
This article analyzes the inclusion of Generative Artificial Intelligence (GAI) in higher education teaching and learning processes. Its objective is to present the incorporation process of GAI into an activity from the course "The Myths That Inhabit Us: From Prometheus to Marvel," a subject offered at the School of Humanities from the Technological Institute of Monterrey. The study evaluated how its use transformed a six-hour assignment into a two-hour one that was much more engaging and of higher academic standards. The methodology employed is a descriptive case study applied to 14 students during the August-December 2024 semester. An activity for creating original myths was redesigned, with instructions shifting from prohibiting GAI to requiring its use through the creation of prompts for video generation. Among the most relevant results is shown a reduction in the assignment time from two to six hours, a significant improvement in the technical quality of the audiovisual products, and the development of digital skills among students.